A Comparative study of transport current loss in HTS coils for superconducting wireless power transfer. (June 2020) - Chen, Hongyi; Li, Quan
Abstract: This paper focuses on the transport current loss modelling for HTS coated conductor coils under high-frequency AC current, which is essential when applying superconducting technology in wireless power transfer system (WPT). The pancake coil, spiral coil and solenoid coil designs were proposed, whose study were carried out based on the Finite Element Method in 2D using H-formulation. The transport current loss in each layer for each coil when applying high-frequency AC current were simulated in the FEM platform. The variation of the transport current loss distribution from different layers of the HTS coated conductor according to changing current input was simulated and compared for different operating frequencies. Finally, the frequency and current dependence of the transport current loss in different layers was shown and compared. The simulation demonstrates that the transport current loss in copper layer could be much higher than the transport current loss in the HTS layer at high current and frequency level due to the skin effect. The results also present that the pancake coil design and spiral coil design could be applied to relatively lower frequency WPT application while solenoid coil design can achieve lowest total loss in higher frequency application. These results are essential when designing HTS coils for WPT system.